Customers’ Response to Service Failure: An Empirical Study on Indonesian Customers - Ellyawati, Jeanne (ASEAN Marketing Journal, 2021)
The purpose of this study is to identify customers’ response to service failure. The response is about why some customers are likely to complain and others are not. This study adopts the concept of customer complaint behavior (CCB) with three-dimensional model: private response, voice response, and third party response. It is also identified the relationships between CCB and customers demographic backgrounds such age, gender and education levels; and their complaining behaviors. Based on a survey of 173 randomly selected of Indonesian consumers who have experienced with service failure, complainers and non-complainers are identified. It is also identified the type of complaint are often perform in facing service failure. The research findings suggested that due to service failure, most customers are likely to engage in a set of multiple responses. Further findings suggested that most complainers who are experiences with service failure are likely to exit.